Seed Germination Behavior of Withania spp. under Different Temperature Regimes. Issue 3 (3rd May 2016) - Kumar, Birendra; Yadav, Richa; Singh, S. C.; Singh, H. P.
ABSTRACT: The genus Withania comprises 23 species, among which only two [ W. somnifera (Ashwagandha) and W. coagulans (Ashutoshbooti)] have been reported from India. Withania spp. dried roots are widely used in traditional system of medicine. Optimal germination potential is essential for commercial growers to justify buying premium-priced seed and ensure acceptable performance of their crop. An experiment was initiated to determine seed germination potential and vigor index of W. somnifera and W. coagulans at three constant (15°C, 20°C, and 25°C) and one alternating (15/35°C) temperature (10/14 h) regimes in Petri dishes, with daily 16 h light (180 lx)/8 h dark photoperiod. Highest germination percentage (92%) and seedling vigor index II (0.2583) were observed at 15/35°C, followed by 15°C (90.7% and 0.1207, respectively) in W. somnifera . Vigor index I was highest (344.5) at 15°C, followed by 15/35°C (319.7) in W. somnifera . In the case of W. coagulans, highest germination percentage (65%), seedling vigor index I (499.9), and vigor index II (0.0609) were recorded at 15°C, followed by 20°C (germination = 55%, vigor index I = 450.01, and vigor index II = 0.0516). This information should help growers in raising a healthy nursery of W. somnifera at 15/35°C or 15°C and 15 or 20°C for W. coagulans .